Characteristics of grassy ELMs and their impact on the divertor heat flux width. (1st September 2022) - Li, Nami; Xu, X.Q.; Wang, Y.F.; Yan, N.; Zhang, J.Y.; Qian, J.P.; Sun, J.Z.; Wang, D.Z.
Abstract: BOUT++ turbulence simulations are conducted for a 60 s steady-state long pulse high β p EAST grassy ELM discharge. BOUT++ linear simulations show that the unstable mode spectrum covers a range of toroidal mode numbers from low- n ( n = 10–15) peeling–ballooning modes (P–B) to high- n ( n = 40–80) drift-Alfvén instabilities. Nonlinear simulations show that the ELM crash is triggered by low- n peeling modes and fluctuation is generated at the peak pressure gradient position and radially spread outward into the scrape-off-layer, even though the drift-Alfvén instabilities dominate the linear growth phase. However, drift-Alfvén turbulence delays the onset of the grassy ELM and enhances the energy loss with the fluctuation extending to pedestal top region. Simulations further show that if the peeling drive is removed, the fluctuation amplitude drops by an order of magnitude and the ELM crashes disappear. The divertor heat flux width is ∼2 times larger than the estimates based on the HD model and the Eich's ITPA multi-tokamak scaling (or empirical Eich scaling) due to the strong radial turbulence transport.